Peran Kreativitas dalam Sistem Kerja dan Kinerja Karyawan Life Hospitality Makassar - Gunawan, Andri; Sihombing, Irene Hanna H.; Rucika, Nyoman Gde Dewa (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the effect of high-performance work systems on employee performance and innovative work behavior, with employee creativity as a mediating variable, at Life Hospitality Group Makassar. This study uses a quantitative approach for an exploratory purpose. The sampling technique used is exhaustive sampling, involving 127 employee respondents. Data analysis was conducted using Structural Equation Modeling Partial Least Square (SEM-PLS). The findings reveal that high-performance work systems have a positive and significant effect on employee performance, innovative work behavior, and employee creativity. Employee creativity also has a significant influence on both performance and innovative behavior. In addition to direct effects, creativity complementary mediates the relationship between high-performance work systems and both outcome variables. These results contribute theoretically to the development of human resource management literature, particularly in the context of implementing high-performance work systems in the Indonesian hospitality sector. Practically, the findings suggest that management at Life Hospitality Group Makassar should prioritize work system strategies that foster creativity to enhance employee performance and innovation.